ТЕХНОЛОГІЯ ОПТИМАЛЬНОЇ ГАРМОНІЇ ВИКОРИСТАННЯ ПРИЙОМІВ ПЕДАГОГІЧНОЇ ТЕХНІКИ ТА ІННОВАТИКИ - ВАЖЛИВИЙ ІНСТРУМЕНТАРІЙ ЕФЕКТИВНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ФАХІВЦЯ (Педагогіка вищої та середньої школи, 2022)
In the given article the author shows the way of using pedagogical methods and innovations. The article deals with different aspects of a teacher readiness to educate taking in account the modern priorities of education.